Risk factors for perinatal stroke in term infants: A case–control study in Australia. (14th February 2023) - Roy, Bithi; Webb, Annabel; Walker, Karen; Morgan, Catherine; Badawi, Nadia; Novak, Iona
Abstract : Aim: The aetiology of perinatal stroke is poorly understood. This study aimed to prospectively confirm the risk factors and identify any previously unknown variables. Methods: A prospective case–control study was conducted in Australia. Univariate odds ratios (ORs), associated 95% confidence intervals (CIs) and multivariable logistic regression models fitted with backwards stepwise variable selection were used. Results: Sixty perinatal stroke cases reported between 2017 and 2019 included 95% (57/60) with multiple risk factors. Univariate analysis identified emergency caesarean section rather than NVD ( P  < 0.01), low Apgar score (<7) at 1, 5 and 10 min of age ( P  < 0.01), resuscitation at birth ( P  < 0.01), abnormal cord blood gas ( P  < 0.01), neonatal infection/sepsis ( P  < 0.01), congenital heart disease ( P <  0.01) and hypoglycaemia ( P  < 0.01) as significant risk factors. Multivariate analysis found smoking during pregnancy (OR: 1.48; 95% CI: 1.09–1.99), 1‐min Apgar score < 7 (OR: 1.54; 95% CI: 1.15–2.08), 10‐min Apgar score < 7 (OR: 1.26; 95% CI: 1.02–1.54) and hypoglycaemia (OR: 1.49; 95% CI: 1.07–2.06). Conclusions: Perinatal stroke is associated with multiple risk factors. Exposure to smoking, 10‐min Apgar score < 7, neonatal infection and hypoglycaemia were independent risk factors. Emergency caesarean section, resuscitation at birth and abnormal cord blood gas were additional risk factors.